Dari Mahasiswa untuk Anak Negeri: Cerita di Balik Posko Ramah Anak - Ramaita Ramaita; Agusmia Intan Sari; Ficko Ari Zulian; Lusiana Suhetsyah; Rizky Rahmawati Ritonga; Suci Rahma Diati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service activity was initiated in response to the lack of beneficial activity options for children in the Jorong Mandahiling and Piliang Laweh areas, Nagari Sumanik, during the school holidays. A "Child-Friendly Post" was created as a temporary space to support children's development through educational games and activities, along with a positive emotional approach. The methods applied were socialization and interactive activities such as creative games, group learning, and reflection sessions facilitated by university students. This activity also involved the local community. The participants consisted of approximately twenty children, ranging from elementary to junior high school age. The evaluation was conducted through direct observation of the children's participation, emotional expression, and growth in social interaction. The results of this activity indicated an approximately 70% increase in soft skills such as self-confidence, communication, and teamwork among the children, as well as increased community involvement in supporting educational activities for children.